Spatial planning in border regions: A balancing act between new guiding principles and old planning traditions? - Karina Pallagst; Andrea Hartz (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
This chapter presents the foundations of spatial planning in the sub-regions of the Greater Region and the Upper Rhine region. It provides a picture of current developments concerning the guiding principles for spatial development and introduces the existing spatial structures of these border regions. Furthermore, the planning systems in Belgium (Wallonia), Germany, France and Luxembourg are described, and differences are identified that necessitate ongoing discussions between the partners about planning traditions and (new) strategies of spatial development.
urn:nbn:de:0156-40970648; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Guiding principles for spatial development; planning systems; Greater Region; Upper Rhine region; cross-border cooperation